1965
DOI: 10.1037/h0021985
|View full text |Cite
|
Sign up to set email alerts
|

Roughness, smoothness, and preference: A study of quantitative relations in individual subjects.

Abstract: A set of 7 surfaces were used as stimuli in a scaling experiment. For 10 Ss individual scales were obtained, by a method of ratio estimation, for (a) roughness, (b) smoothness, and (c) preference. The main results were: (a) For all Ss roughness was approximately a power function of the physical stimulus variable denned as the coefficient of friction. The exponent of the function varied greatly between Ss but exceeded 1 in almost all cases, (b) For nearly all Ss smoothness was approximately the inverse of rough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
58
4

Year Published

1970
1970
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 17 publications
11
58
4
Order By: Relevance
“…The association of smoothness with friction force is in agreement with other measurements of the coefficient of friction on the fingers (Ekman, Hosman, & Lindström, 1965) and in the mouth (Kokini et al , 1977). Earlier studies also seem to show that the smoothness of solid surfaces is inversely proportional to roughness (Stevens & Harris, 1962).…”
Section: Thus According To Equation 10supporting
confidence: 77%
“…The association of smoothness with friction force is in agreement with other measurements of the coefficient of friction on the fingers (Ekman, Hosman, & Lindström, 1965) and in the mouth (Kokini et al , 1977). Earlier studies also seem to show that the smoothness of solid surfaces is inversely proportional to roughness (Stevens & Harris, 1962).…”
Section: Thus According To Equation 10supporting
confidence: 77%
“…Dorsch, Hsiao, Johnson, and Yoshioka (2001) used subjective magnitude ratings to examine roughness perception during the active exploration of sandpaper surfaces. In agreement with previous work examining roughness perception using sandpaper surfaces (Ekman, Hosman, & Lindstrom, 1965;Hollins & Risner, 2000), they found that perceived roughness increased with surface roughness. That is, sandpaper surfaces with lower grit values, which have larger particles, were perceived as being rougher than those with higher grit values (smaller particles).…”
supporting
confidence: 81%
“…For example, with direct touch, the perceived roughness of gratings has been found to increase as groove width increases and to decrease as ridge width increases (Lederman and Taylor 1972;Sathian et al 1989;Yoshioka et al 2001), and the perceived roughness of sandpapers is a power function of particle size (Ekman et al 1965;Hollins and Risner 2000). In other studies using embossed dot patterns, the relationship between perceived roughness and dot size, height, and spacing has been shown to be complex.…”
Section: What Are Roughness Hardness and Stickiness?mentioning
confidence: 95%